AIRCRAFT COLLISION RISK ASSESSMENT IN THE AIRPORT AREA - Нестерова, Л. М. (Proceedings of National Aviation University (archive), 2021)
Flight safety criteria in the aerodrome area are considered. Three evaluation models are analyzedcollision of aircraft in the aerodrome area